Genetic loci influencing kidney function and chronic kidney disease. - Chambers, J; Zhang, W; Lord, G; van der Harst, P; Lawlor, D; Sehmi, J; Gale, D; Wass, M; Ahmadi, K; Bakker, S; Beckmann, J; Bilo, H; et al. (2010)
Using genome-wide association, we identify common variants at 2p12-p13, 6q26, 17q23 and 19q13 associated with serum creatinine, a marker of kidney function (P = 10(-10) to 10(-15)). Of these, rs10206899 (near NAT8, 2p12-p13) and rs4805834 (near SLC7A9, 19q13) were also associated with chronic kidney disease (P = 5.0 x 10(-5) and P = 3.6 x 10(-4), respectively). Our findings provide insight into metabolic, solute and drug-transport pathways underlying susceptibility to chronic kidney disease.